Rate of progress to flowering in annual species of genus Trifolium grown for silage in Galicia (NW of Spain) as affected by sowing date - Flores-Calvete G.; Valladares-Alonso J.; Pereira-Crespo S.; Díaz-Díaz N.; Díaz-Díaz D.; Resch-Zafra C.; Fernández-Lorenzo B.; Dagnac T.; Crecente-Campo S.; Salvatierra-Rico J.A. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
With the objective of gaining insight on the relationship between sowing date and the onset of flowering of annual Trifolium species in Galicia (NW Spain), commercial genotypes of arrowleaf clover (5), balansa clover (5), berseem clover (2), crimson clover (6), persian clover ssp. majus (2) and ssp. resupinatum (3) were sown in small plots from 15th September 2012 to 15th April 2013 at monthly intervals following a splitplot design with two replications. The time from sowing to flowering, measured as days after planting (DAP) was significantly affected by species and sowing dates, ranging from 175 to 124 days for the latest (berseem clover) and the earliest (balansa clover) species and from 218 to 79 days for the September and April sowings dates, respectively, which represented the least and the most inductive flowering conditions. Although a significant effect in DAP was detected for the interaction species x sowing date, the earliness of annual clovers studied ranked in a similar way (balansa clover > persian clover ssp. resupinatum and crimson clover > arrowleaf clover > persian clover ssp.majus > berseem clover) across sowing dates. Phenological models that related the rate of progress to flowering (DAP)-1 with temperature and photoperiod during the growing cycle accounted for 65% and 90% of the variability, showing that in the agroclimatic conditions of NW Spain flowering of annual clovers was more sensitive to photoperiod than to temperature.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)